The Comparison of Childrenâ€™s Anthropometrics and Motor Performance Relative Body Mass Index using Principle Component Analysis - Razali Abdullah, Mohamad; Ayob, Nuruaslizawati; Musliha Mat-Rasid, Siti; Juahir, Hafizan; Muazu Musa, Rabiu; Bisyri Husin Musawi Maliki, Ahmad; Azura Kosni, Norlaila; Afzan Aziz, intan; Syaiful Nizam Abu Hassan, Mohd; Khairi Zawi, Mohd; Alias, Norzulaika; Azahari, Hanisah (International Journal of Engineering and Technology, 2018)
This study aims to compare dominant factors of anthropometrics and motor component among children relative body mass index. A total 5819 primary school children (3243 boys and 2576 girls) aged 7.30Â±0.28 years old were subdivided into four groups according their Body Mass Index (BMI) namely underweight group (UWG), normal weight group (NWG), overweight group (OWG) and obese group (OBG). The parameters involved in this study are weight, height, standing broad jump (SBJ), sit and reach (SAR), hand wall toss (HWT) and 20 meter run (20MR). Method of Principle Components Analysis (PCA) was employed to ascertain the domain factors parameters for each BMI group. For boys and girls, initial PCA identifies two components with higher Eigen value (> 1). In first component VF1 for boys and girls, PCA after varimax rotation revealed two varifactors that are weight (> 0.90) and height (> 0.80) for all BMI group. Otherwise, second component VF2 for boys and girls revealed high factor loading on low muscular strength, hand-eye coordination and speed. This study indicates there is direct effect between motor proficiency and BMI among preschool population and revealed that primary school children with high body mass may have lower motor proficiency on explosive strength, coordination and speed compared with normal body mass.Â